Quality Assurance and Shelf-Life Extension of Kinnow Mandarin Fruit Under Supermarket Conditions. Issue 1 (2nd January 2016) - Mahajan, B. V. C.; Singh, Rupinder; Kumar, Mahesh
ABSTRACT: Kinnow mandarin (Citrus nobilis × Citrus deliciosa) fruits were harvested at firm mature stage, packed in paper-molded trays, and tightly sealed in different packaging films commercially available in the market, viz. cryovac heat shrinkable RD-106 film (15 µ), low density polyethylene film (LDPE, 25 µ), and high density polyethylene film (HDPE, 10 µ). After packaging, the fruits were stored at supermarket conditions (18 to 20 °C; 80–85% RH). There were five storage intervals and for each storage interval three packs (six fruit in each pack) were prepared for each packaging film. In total, 60 packs were made for all packaging films including control to lay out this experiment. The fruits were evaluated for various quality attributes periodically. The shrink film helped in reducing the loss in weight and firmness and maintained the various quality attributes, such as total soluble solids, acidity, ascorbic acid, and carotene content of the fruit juice, during shelf life better than other packaging films and unwrapped control fruits. The in-package gaseous composition (O2 and CO2 ) in shrink film packed fruits was found to be at a desired level, which resulted in maintaining pleasant flavor of the fruits. On the other hand, LDPE and HDPE film accumulated a very high level of CO2, which led to formation of a fermenting odor in the package. The data revealed that RD-106 film proved quite effective in prolonging the shelf life and maintaining the quality of Kinnow fruits for 25 days under supermarket conditions as opposed to 10 days only in the case of unpacked control fruits.